From Discovery to Revelation: Midrashic Poetics in Aggadat Vayar by Mendele Mocher Sforim - Dayan Codish, Moria (MiKAN, 2022)
In this article, the author examines two nearly forgotten works by Mendele Mocher Sforim in an attempt to demonstrate how rabbinic and midrashic literature has influenced Modem Hebrew literature. By revealing the complex system of links between Mendele’s works and the midrashic style, the author seeks to challenge the ingrained hermeticity of the modem distinction between premodem literature and modem literature, and discuss literature in terms of continuity instead. The two works the articles centers on are sequels to Mendele’s The Travels of Benjamin III. These are the short story Aggadat Vayar and its proem Aggadot Ha-Admonim (Legends of the Red-Complexioned), parodic midrashic texts that chronicle the continued travels of Benjamin and Senderl and their wondrous discovery of the Ten Lost Tribes of Israel. Does the parody these legends convey reflect the farcical aspects of scholasticism, the negation of reality, and the faults and limits of the midrashic technique? If so, and if Mendele is well aware of the limits of midrash, what motivates him to make constant use of it? Through an analysis of the stories, the author seeks to resolve this ambivalence by identifying support for a halfway model in Mendele’s legends, according to which midrash, like snake venom, gives life when taken in moderation and brings death when consumed in excess.